1969
DOI: 10.12669/pjms.321.8476
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Dysfunction in General Population of Khyber Pakhtunkhwa, Pakistan

Abstract: Objectives:The objective of this research was to elucidate some of the major relation of thyroid dysfunctions, keeping in view the various selected demographic details of included patients.Methods:This study was approved by the ethical committee of Post Graduate Medical Institute (PGMI) Hayatabad Medical Complex Peshawar, and was conducted in the Institute of Radioactive Nuclear Medicine (IRNUM) Peshawar. The blood samples were collected, followed by their analysis for triiodothyronine (T3), tetraiodothyronine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
1
11
1
Order By: Relevance
“…This may not be surprising as hyperthyroidism is more prevalent in our region as compared to hypothyroidism. 27 , 28 These findings also correlate with study done in Pakistan by Lalani S and in India by Kameswaramma K et al, while studies done in Nepal by Rijal B et al and in Pakistan by Naib et al shows high prevalence of hypothyroidism as compared to hyperthyroidism in infertile women. 12 , 19 , 29 , 30 …”
Section: Discussionsupporting
confidence: 74%
“…This may not be surprising as hyperthyroidism is more prevalent in our region as compared to hypothyroidism. 27 , 28 These findings also correlate with study done in Pakistan by Lalani S and in India by Kameswaramma K et al, while studies done in Nepal by Rijal B et al and in Pakistan by Naib et al shows high prevalence of hypothyroidism as compared to hyperthyroidism in infertile women. 12 , 19 , 29 , 30 …”
Section: Discussionsupporting
confidence: 74%
“…That might be encountered in resource poor settings that emphasizes on the fact that iodine deficiency still remains the top most cause of thyroid disorders on the African continent [12]. Furthermore the proportion of patients with malignancy in this study was 13.1 which contrasts with what is reported in Europe North America where the malignancy rate is 5% [20]. In another study carried out in India by Khageswar Rout, Chinmay Sunder Ray, Subrat Kumar Behra and Rudranarayan Biswal with a sample size of 76 patients, demonstrated that colloid goiter was the most common among the thyroid swellings followed by colloid goiter with cystic degeneration [17].…”
Section: Discussioncontrasting
confidence: 64%
“…The current American Thyroid Association recommendations take account of nodule size, thyroid function test and sonographic features, and, despite cytological diagnosis of category III, the nodule may be surgically excised prompted by clinical or radiological findings, thereby raising the number of AUS‐malignant cases. Pakistan, like India, is on the Himalayan belt, where prevalence of thyroid nodules is higher and multiple goitrogens in the environment pose greater risk of goitres as well as worrisome nodules, 29,30 which may be one of the reasons behind slightly higher malignant diagnoses in the AUS/FLUS category.…”
Section: Discussionmentioning
confidence: 99%